Reduction in cost of using CAD/CAE systems : a study of local civil and structural consulting firms - Soh, Eng Teong. (2009)
This report describes a model that was found to be suitable to perform cost savings analysis in using CAD/CAE systems. The model is further developed for typical civil and structural design offices' environment. The evaluation process leading to a purchase of a new system or upgrade of an existing system usually requires a scheme for cost justification. This report looks into the cost structure of the computer systems, how the costs may be analysed, and the way the systems justify the investment in computer systems by using productivity improvement concept.